2017
DOI: 10.1073/pnas.1612106114
|View full text |Cite
|
Sign up to set email alerts
|

Full atomistic reaction mechanism with kinetics for CO reduction on Cu(100) from ab initio molecular dynamics free-energy calculations at 298 K

Abstract: A critical step toward the rational design of new catalysts that achieve selective and efficient reduction of CO 2 to specific hydrocarbons and oxygenates is to determine the detailed reaction mechanism including kinetics and product selectivity as a function of pH and applied potential for known systems. To accomplish this, we apply ab initio molecular metadynamics simulations (AIMμD) for the water/Cu(100) system with five layers of the explicit solvent under a potential of −0.59 V [reversible hydrogen electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
595
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 493 publications
(637 citation statements)
references
References 52 publications
39
595
2
1
Order By: Relevance
“…Our previous QM metadynamics calculations with full solvent showed that a CO binding energy of 0.70 eV is sufficient to keep CO on the surface at potentials less negative than -0.91 V (RHE). 15 We find that this combination of binding sites reduces the *OCCOH formation energy to 0.52 eV, which is the best performance among the active surface sites investigated here.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our previous QM metadynamics calculations with full solvent showed that a CO binding energy of 0.70 eV is sufficient to keep CO on the surface at potentials less negative than -0.91 V (RHE). 15 We find that this combination of binding sites reduces the *OCCOH formation energy to 0.52 eV, which is the best performance among the active surface sites investigated here.…”
Section: Introductionmentioning
confidence: 66%
“…24 In our recent work, we carried out full solvent QM based metadynamics to determine the RDS for C-C coupling, which we also found associated with the process of first electron transfer. 15,25 Consequently, we take the formation energy of *OCCOH as a descriptor to characterize the performance of surface sites toward C2 production. The experimental work of Verdaguer et al presented a correlation between strong CO binding sites and high CO reduction activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous mechanistic studies revealed that the reaction pathways for CH 4 and C 2 H 4 differ at the bound CO* intermediate [48][49][50][51] .…”
Section: Nature Catalysismentioning
confidence: 99%
“…[3][4][5][6] Synthesis of these products will by necessity require CÀHa nd CÀCb ond formation events.H owever,l ittle is understood about the processes taking place at the electrode surface.Specifically,in forming abond, two distinct surface-reaction mechanisms can be in play:surface-bound species can react with each other in what the heterogeneous catalysis field calls aL angmuir-Hinshelwood (LH) step or asurface-bound species can react with as pecies in solution in what is termed an Eley-Rideal (ER) step. [8] Insight into this mechanistic distinction is essential for the design of efficient CO 2 reduction catalysts.For example,inan ER mechanism leading to methane,s imply increasing the surface concentration of CO at the expense of Hadsorption is sufficient to promote higher-order product formation relative to H 2 evolution. Analogous mechanisms can be envisioned for CÀCbond formation leading to ethylene.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16] However,t hese studies alone are unable to parse reaction mechanisms.I ndeed, studies of the COdependent kinetics of higher-order product formation are uniquely suited to distinguish different mechanistic possibilities because they directly probe kinetically relevant intermediates and provide reaction orders for each product. [8,17,18] However,w hile excellent studies have investigated the pH, electrolyte cation, and crystal facet dependence of the reaction, [19][20][21][22][23][24][25][26][27][28][29] investigations of the CO-dependent kinetics have thus far been hampered by the low solubility of CO in aqueous electrolytes (1.1 mm), [30] which severely restricts the concentration range over which activation-controlled CO reduction kinetics can be probed. Furthermore,t he mechanistic regimes become distinguishable at near saturation CO coverage,t herefore requiring an experimental approach that fosters strong CO binding to the Cu surface.…”
mentioning
confidence: 99%